Stomata Diversity Profile of Several Coffee Species at the Indonesian Coffee and Cocoa Research Center - Hapsari, Tasya; Munandar, Kukuh; Wibowo, Ari (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2023)
Stomata are a special part of plants, namely a number of leaf epidermal cells, both the upper and lower surface epidermis of the leaves. Stomata function as a place for CO2 to enter from the air in the process of photosynthesis, where respiration and transpiration take place so that stomata are an important tissue in plant metabolic processes. Observing stomata using a microscope is an effective and easy way to determine the type of stomata in angiosperm plants. This research was conducted on November 19 2022 with the aim of determining the type and diversity of stomata on several types of coffee plants at the Indonesian Coffee and Cocoa Research Center. The method used in this research is an exploratory survey method, while the replica method is used to look at leaf stomata, namely applying nail polish to the leaf surface and identifying the type of stomata using a qualitative descriptive method. The survey found that there were 9 types of coffee plants at the Indonesian Coffee and Cocoa Research Center. The results of the research show that the type of stomata on coffee plants based on the number and arrangement of neighboring cells is classified as a parasitic type. This can be seen from the presence of two neighboring cells surrounding the guard cell and the location of these cells parallel to the guard cell.